A study of the Press Council in Indonesia and its implications for Malaysia. - Tong, Kooi Chin. (2008)
The relationship between press freedom and press accountability has been more hotly discussed lately in the Southeast Asian context due to the changes in media scenario. And it was in this atmosphere that press councils came into the picture and were expected to play a role in handling the delicate balance between press freedom and social responsibility. Very little research has been conducted on the effects of press councils, and most of it was mainly on western models. To bridge the gap, this thesis examined the press council’s characteristics and effects in Indonesia, which has the longest history of press councils in Southeast Asia, and through an analysis of its experiences, assessed whether Malaysia’s newly proposed media council is feasible and beneficial. How was the performance of Indonesia’s press council on such a tightrope? Can this concept work in Malaysia?